Aplikasi Penentuan Lokasi untuk Usaha Lapangan Futsal di Kecamatan Bangil Menggunakan Metode Fuzzy Tsukamoto - Muhammad Alfian Nuris Shobah; Edy Santoso; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The system is built with the aim to help predict the results of operations of futsal in Bangil. In futsal open businesses have competitor input, the number of residents, the facilities, the size of the field. And this system produces an output stratification business opportunities, namely the village suitable for open futsal field. These systems are processed using fuzzy logic reasoning method Tsukamoto. The purpose application made to function as expected that is able to help resolve problems that arise and are difficult to solve because of an uncertainty which is very thin difference. From the data obtained will be an Tsukamoto fuzzy calculation that produces an output to be able to predict the circumstances that will occur from the input-input affecting. From the test results the decision-making system of determining the right location to open futsal in Kecematan Bangil with Tsukamoto method to 7 futsal some courts have precisely select locations, but the majority is still not right.